Regulation of monoubiquitinated PCNA by DUB autocleavage. - Huang, T; Nijman, S; Mirchandani, K; Galardy, P; Cohn, M; Haas, W; Gygi, S; Ploegh, H; Bernards, R; D'Andrea, A (2006)
Monoubiquitination is a reversible post-translational protein modification that has an important regulatory function in many biological processes, including DNA repair. Deubiquitinating enzymes (DUBs) are proteases that are negative regulators of monoubiquitination, but little is known about their regulation and contribution to the control of conjugated-substrate levels. Here, we show that the DUB ubiquitin specific protease 1 (USP1) deubiquitinates the DNA replication processivity factor, PCNA, as a safeguard against error-prone translesion synthesis (TLS) of DNA. Ultraviolet (UV) irradiation inactivates USP1 through an autocleavage event, thus enabling monoubiquitinated PCNA to accumulate and to activate TLS. Significantly, the site of USP1 cleavage is immediately after a conserved internal ubiquitin-like diglycine (Gly-Gly) motif. This mechanism is reminiscent of the processing of precursors of ubiquitin and ubiquitin-like modifiers by DUBs. Our results define a regulatory mechanism for protein ubiquitination that involves the signal-induced degradation of an inhibitory DUB.